The impact of diversity field forums: improving farmer management of millet and Sorghum in Mali - Gotor, Elisabetta; Cherfas, J. (2011)
The brief summarizes an evaluation of the impact of one participatory research effort known as diversity field forums (DFFs). DFFs bear some similarities to farmer field schools - an approach to improving crop management practices that involves teaching groups of farmers how to solve problems, set priorities and conduct research through facilitated, handson sessions in fields allocated by the farming community. The Forums aim to strenghten the capacity of farmers to understand, analyse and manage their own plant genetic resources by creating a physical space that facilitates the exchange of ideas among farmers, extension agents and researchers and encourages farmers to experiment with different varieties and production approaches. The project, Empowering Sahelian farmers to leverage their crop diversity assets for enhanced livelihood strategies, was funded by the International Fund for Agricultural Development (IFAD) from 2005, coordinated by Bioversity International and implemented by a combination of local, national and international organizations. Villagers designed and conducted the field trials, with technical support from project staff, on land that they had set aside for the purpose. Farmers studied both modern varieties and landraces.